Early Detection of Sepsis and NEC Using Serial Vital Sign Trends (HR, SpO₂, RR) on Standard NICU Monitors in Preterm Neonates: Sepsis and NEC Using Serial Vital Sign Trends on Standard NICU Monitors - Hakeem, Danish; Iqbal, Javeria; Saad, Muhammad; Tahir, Tujza; Jamil, Arshad; Kainat khan (Pakistan Journal of Health Sciences, 2025)
Preterm neonates are at high risk for sepsis and necrotizing enterocolitis (NEC), but early signs are often subtle, delaying diagnosis and worsening outcomes. Objectives: To evaluate whether trends in routinely monitored heart rate (HR), respiratory rate (RR), and oxygen saturation (SpO₂) predict sepsis and NEC and to examine their association with NICU stay, mortality, and discharge outcomes. Methods: A prospective observational cohort study was conducted among 103 preterm infants (<37 weeks’ gestation) admitted to a tertiary NICU with continuous multi-parameter monitoring. HR, RR, and SpO₂ trends were compared between infants with sepsis/NEC and those who remained stable. Outcomes were analyzed using t-tests, Mann–Whitney U tests, Chi-square tests, and logistic regression. Cox regression identified mortality predictors, and Kaplan–Meier curves compared survival between groups. Results: Sepsis occurred in 22.3% and NEC in 7.8% of neonates. Female infants had lower odds of sepsis/NEC (adjusted OR = 0.23, 95% CI: 0.07–0.74, p=0.013). Sepsis/NEC was linked to longer NICU stay (21.6 ± 6.8 vs 11.9 ± 4.4 days, p<0.001) and higher mortality (30.4% vs 10.0%, p=0.014). Cox regression confirmed sepsis/NEC as an independent predictor of mortality (HR = 0.084, p=0.005). Conclusions: Routine vital sign trends alone were insufficient for early detection, but their association with adverse outcomes underscores the potential of enhanced monitoring and predictive modeling to enable earlier recognition and improved survival.